PENGARUH PENJUALAN, BIAYA OPERASIONAL, TOTAL HUTANG, PERPUTARAN PERSEDIAAN TERHADAP LABA BERSIH PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2014 - 2017 - Jholant Bringg Luck Amelia Br. Sinaga; Murni Sihotang; Okta via; Jessica Desiani; Hen dry (Universitas Islam Islam Sumatera Utara, 2020)
Manufacturing companies are one of the developing companies in Indonesia. This study aims to determine the effect of sales, operational costs, total debt and inventory turnover on profits in manufacturing companies in 2014-2017. The sample used in this study was 27 samples in a period of 4 years so that 108 sample units of manufacturing companies were listed on the Indonesia Stock Exchange in 2014-2017. The data obtained is secondary data using the documentation method. Based on the results of testing F sales test hypotheses, operational costs, total debt and inventory turnover simultaneously affect earnings because the value of Fcount Ftable is 67.701 3.28. From the results of the t test, sales and operating costs have a positive effect on earnings because the value of tcount 6.051 t table 1.983 so that tcount t table for sales and tcount 2.255 t table 1.983 for operational costs. Whereas, total debt and inventory turnover negatively affect earnings because the value of tcount -1.836 ttable 1.983 for total debt and tcount 1.916 ttable 1.983 for inventory turnover.